2021
DOI: 10.3389/fonc.2021.693704
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Pathological Complete Response in a Brain-Metastatic Lung Squamous Cell Carcinoma Patient With Long-Term Benefit From Chemo-Immunotherapy

Abstract: Immune checkpoint inhibitors have brought long-term survival benefit in advanced non-small cell lung cancer patients without driver gene mutations. Even after withdrawal of immunotherapy for a maximum of two years, some patients still benefit from this therapy and the reason is not fully clear. Results from several neoadjuvant trials indicated that in resectable lung cancer patients, neoadjuvant immunotherapy or chemo-immunotherapy led to major or complete pathological responses in a high proportion of tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…25 Furthermore, 'real-world evidence' on neoadjuvant immuno(chemo)therapy in oligometastatic patients is restricted to few cases reporting encouraging outcome. [26][27][28] To assess the efficacy of neoadjuvant immuno(chemo)therapy in a broad real-world NSCLC population, we performed a multicentre retrospective analysis (KOMPASSneoOP) of pathological and radiological response and survival after resection following neoadjuvant immuno(chemo)therapy in patients with stage IIB-IVB NSCLC (oligometastatic). 5 Furthermore, we addressed the open question of the necessary number of cycles of neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Furthermore, 'real-world evidence' on neoadjuvant immuno(chemo)therapy in oligometastatic patients is restricted to few cases reporting encouraging outcome. [26][27][28] To assess the efficacy of neoadjuvant immuno(chemo)therapy in a broad real-world NSCLC population, we performed a multicentre retrospective analysis (KOMPASSneoOP) of pathological and radiological response and survival after resection following neoadjuvant immuno(chemo)therapy in patients with stage IIB-IVB NSCLC (oligometastatic). 5 Furthermore, we addressed the open question of the necessary number of cycles of neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, ‘real-world evidence’ on neoadjuvant immuno(chemo)therapy in oligometastatic patients is restricted to few cases reporting encouraging outcome. 26 28…”
Section: Introductionmentioning
confidence: 99%
“…In this case, what was surprising was that the patient presented with MSS and negative PD-L1 expression who was supposed to be relatively insensitive to immunotherapy and found that she still had an excellent response to anti-PD-1 antibody combined with chemotherapy, indicating that other mechanisms than MSI and PD-L1 positive might account for the responsiveness to ICIs (28). As shown in Table 1, this phenomenon has also been reported in gallbladder carcinoma (14), leiomyosarcoma (15), non-small cell lung cancer (21), gastroesophageal junction carcinoma (28), melanoma (32), and small cell lung cancer (37). Previous studies demonstrated that chemotherapy might be able to enhance anticancer immunity by reactivating immune effector cells, stimulating tumor antigen presentation, and eliminating immune suppressor cells, thus resulting in a synergistic anticancer effect compared with the anti-PD-1 monotherapy (58,59).…”
Section: Discussionmentioning
confidence: 69%
“…As such, an increasing number of cancer patients have benefitted from immunotherapy. [ 2 , 3 ] In recent years, great achievements have been made regarding immune checkpoint inhibitors in research on neoadjuvant immunotherapy. Among them, nivolumab's performance has been particularly eye-catching, bringing significant clinical benefits to some patients with early and middle stage tumors, and becoming a hot topic in the field of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Some programmed death-1 (PD-1)/programmed death receptor ligand-1 (PDL-1) inhibitors can activate the autoimmune system and inhibit tumor progression. As such, an increasing number of cancer patients have benefitted from immunotherapy [2,3] . In recent years, great achievements have been made regarding immune checkpoint inhibitors in research on neoadjuvant immunotherapy.…”
Section: Introductionmentioning
confidence: 99%